Features of the long-term dynamics of development hydro/chemical parameters of the water of the Shershnevsk Reservoir - Anna V. Kravtsova; Nadezhda I. Khodorovskaya; Vladislav A. Yachmenev; Vasilina V. Bazhenova (Водное хозяйство России: проблемы, технологии, управление)
The Shershnevsk reservoir is the only source of economic and drinking water supply in the Chelyabinsk agglomeration. The reservoir and its catchment area are subjected to intense man-made and recreational loads, which affects the water quality and the status of the reservoir ecosystem. The purpose of this work is to study the features of the long – term dynamics of the development of hydro/chemical indicators of the water of the Shershnevsk reservoir in order to determine trends in the dynamics of the state of the reservoir ecosystem and propose measures to preserve the operational properties of the reservoir.